Perubahan Strategi dan Organisasi - Shofi Aliza Putri; Manna Wassalwa (MES Bogor, 2023)
The dynamics of changing times will continue to progress, it will affect the development of the organization. The organization has developed accompanied by a better direction of change. The reason for the importance of the organization because change is a sign of life, change must give hope and development is an attempt to adjust to new things. to survive, the organization must direct its members to adapt well. Keywords: development. organization, strategic